Synthesis of conjugated covalent organic frameworks/graphene composite for supercapacitor electrodes. Issue 35 (16th March 2015) - Wang, Peiyuan; Wu, Qiong; Han, Lifeng; Wang, Shen; Fang, Shaoming; Zhang, Zhihong; Sun, Shumin
Abstract : A novel imine-linked covalent organic framework on graphene composite with excellent electrochemical properties was conveniently synthesized in one step. Abstract : A novel composite with imine-linked covalent organic frameworks on graphene was synthesized in one step with the amine functionalized reduced graphene oxide as the support. The excellent electrochemical properties of this composite can be ascribed to the synergistic effect of the introduction of covalent organic frameworks as well-dispersed nanoscale deposits on the conductive graphene surfaces.